PENGARUH INDEPEDENSI DAN PROFESIONALISME DALAM MENDETEKSI FRAUD (STUDI KASUS PADA KANTOR AKUNTAN PUBLIK DI JAKARTA) - DANIEL HARA TUA LUMBAN GAOL; MANATAP BERLIANA LUMBAN GAOL; VEBRY M. LUMBAN GAOL (LP2MTBM MAKARIOZ, 2022)
The purpose of this study was to examine the effect of independence and professionalism in detecting fraud at a Jakartapublic accounting firm. The research method is classified into quantitative correlational research, namely research withstatistical methods that measure between two or more variables. The population in this study are auditors who work. Thesample in this study used a judgment sampling technique with a total of 41 auditors working in several public accountingfirms in Jakarta. The results show that independence has no significant effect in detecting fraud at KAP in Jakarta,professionalism has a significant positive effect in detecting fraud at KAP in Jakarta, so it can be concluded thatindependence has no significant effect in detecting fraud, while professionalism has a positive effect in detecting fraud forauditors. public accounting firm in Jakarta.